Selenium in Ruminant Diets: An Antioxidant, Hormonal Regulator, and Environmental Nutritional Component: Subject Review - Omer, Esam Saeed; Rebat, Salam Ketab; Hussein, Zakariya Ahmed; Abdulazeez, Sarmad Talib (Journal of Science in Medicine and Life, 2025)
Selenium is considered a trace element and is biologically important in the health and behavior of ruminant animals., as it helps protect cells from oxidative damage, improves the efficiency of the immune resistance, and enhances reproductive functions. This study examines the role of selenium in biological technology for ruminants by analyzing its chemical forms (organic and inorganic) and its differing availability and bioavailability, to increase and improve growth, production and fertility. In addition, selenium's interactions with other mineral elements in feed, and its environmental complications resulting from its increased use, are important. The study discusses the role of selenium as an effective integrated antioxidant in proteins such as glutathione peroxidase. Its effect is in protecting against oxidative stress and strengthening disease resistance. The extent of its effect on absorption and metabolism within the digestive system of ruminants is also detailed, as well as its effect on hormones and reproductive functions in males and females. Highlighting the importance of regulating the levels of selenium added to diets to avoid selenium poisoning and the extent of full benefit without negative impact. The thoughtful use of selenium, specifically in its organic forms, represents an effective model for improving animal health and continuous production, provided that the intended safe limits are estimated and the environmental factors affecting its increase are maintained.